Suara Kebebasan Dalam Cerita Pendek Kafanu Al - Ustazi Karya Haifa Bitar: Kajian Ginokritik Elaine Showalter - Nizar, Mohammad; Dewi Asih, Kusuma (PT. Kreasi Karya Majakata, 2023)
This article attempts to express feminist literary criticism of the writer Haifa Bitar in one of his works, in the short story anthology